Gender outlook on advisory system, entrepreneurship and graduate employability - Rokis, Rohaiza (Scientific Research, 2018)
Unemployment is higher among young workers, particularly females. Part of the solution rests at the tertiary levels. The article views that undergraduates must have career knowledge, particularly in entrepreneurship, upon their graduation. This can be achieved through students’ advisory system at each university. The International Islamic University Malaysia (IIUM) is chosen as a case. The research is conducted in the view that IIUM’s advisory system is not used to the maximum. The mentors (teachers/lecturers) and mentees (undergraduates) are not really able to utilize the advisory system in the most effective way. It has an unfixed sense of connectedness in the life of the undergraduates. This situation may lead them graduated unprepared for the employment. Thus, it is sensible to investigate the possibility of utilizing the IIUM’s advisory system towards employment prospects, using entrepreneurship modules for the benefits of female and male students. The samples are chosen among IIUM students within the age group of 22 to 26 for survey and interview designs. The design of the survey is to obtain statistics that describes particular descriptive aspects of the students, entrepreneurship embedded content in the academic program and the advisory system. In addition, the design of the interview is to capture the qualitative opinions of the students in regards to their aspiration in career upon graduation through the advisory system. This research concludes that an effective advisory system leads to career planning and employment chances particularly entrepreneurship among female graduates. The advisory system must foster the culture of connectedness between mentor-mentee in entrepreneurial skills for greater undergraduate employability prospects.